2020
DOI: 10.1039/d0sc00227e
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic consequences of Tyr to Trp mutations in the cation–π-mediated binding of trimethyllysine by the HP1 chromodomain

Abstract: In this work, we experimentally validate that tryptophan provides the strongest cation–π binding interaction among aromatic amino acids and also lend insight into the importance of residue identity in trimethyllysine recognition by reader proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
6
15
0
Order By: Relevance
“…A similar effect is also noted for interactions of ammonium ions with phenol and indole. Consistent with earlier work, [14] we also note that the methylated ammonium ions bind most strongly to indole, followed by phenol and benzene. Overall, we find that in the scenario where methyl groups are added away from the dimer interface, dimer affinities drop substantially.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…A similar effect is also noted for interactions of ammonium ions with phenol and indole. Consistent with earlier work, [14] we also note that the methylated ammonium ions bind most strongly to indole, followed by phenol and benzene. Overall, we find that in the scenario where methyl groups are added away from the dimer interface, dimer affinities drop substantially.…”
Section: Resultssupporting
confidence: 92%
“…We also examine the effect of ammonium methylation on its dimerization energies with two other aromatic groups, phenol and indole. These molecules represent tyrosines and tryptophans, respectively, found frequently in binding pockets of methyllysine reading domains, [49] and there are ongoing efforts to understand their relative roles in binding and selectivity [12,14] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). These results implicated that Trp and Arg were essential in the cation-π and π-cation interactions, which was consistent with the previous results [33][34][35].…”
Section: Data Content and Analysissupporting
confidence: 93%
“…HP1′s aromatic cage residues were individually substituted on position 24 and 48 with tyrosine analogues to further establish the individual contributions of these two residues in recognition of Kme3, revealing that the residues do not equally contribute towards cation–π binding and that efficient association depends on contact between Tyr residues and Kme3 [ 152 ]. Additionally, the Tyr residues present in the HP1 aromatic cage were substituted by Trp to investigate if this mutation could increase the binding strength to the Kme3-containing substrate, and more generally the conservation of aromatic residues within aromatic cages [ 153 ]. It was found that the mutation Y24W was not perturbing and allowed in the binding pocket, leading to a −5 kcal mol −1 stronger binding.…”
Section: Reading Kme3mentioning
confidence: 99%